How Common is Subsequent Posterior Tibial Tendon Dysfunction or Tarsal Tunnel Syndrome After Ankle Sprain Injury? - Foster, Kaitlyn S.; Greenlee, Tina A.; Young, Jodi L.; Janney, Cory F.; Rhon, Daniel I. (The Journal of Knee Surgery, 2022)
Posterior tibial tendon dysfunction (PTTD) and tarsal tunnel syndrome (TTS) are debilitating conditions reported to occur after ankle sprain due to their proximity to the ankle complex. The objective of this study was to investigate the incidence of PTTD and TTS in the 2 years following an ankle sprain and which variables are associated with its onset. In total, 22,966 individuals in the Military Health System diagnosed with ankle sprain between 2010 and 2011 were followed for 2 years. The incidence of PTTD and TTS after ankle sprain was identified. Binary logistic regression was used to identify potential demographic or medical history factors associated with PTTD or TTS. In total, 617 (2.7%) received a PTTD diagnosis and 127 (0.6%) received a TTS diagnosis. Active-duty status (odds ratio [OR] 2.18, 95% confidence interval [CI] 1.70–2.79), increasing age (OR 1.03, 95% CI 1.02–1.04), female sex (OR 1.58, 95% CI 1.28–1.95), and if the sprain location was specified by the diagnosis (versus unspecified location) and did not include a fracture contributed to significantly higher (p < 0.001) risk of developing PTTD. Greater age (OR 1.06, 95% CI 1.03–1.09), female sex (OR 2.73, 95% CI 1.74–4.29), history of metabolic syndrome (OR 1.73, 95% CI 1.03–2.89), and active-duty status (OR 2.28, 95% CI 1.38–3.77) also significantly increased the odds of developing TTS, while sustaining a concurrent ankle fracture with the initial ankle sprain (OR 0.45, 95% CI 0.28–0.70) significantly decreased the odds. PTTD and TTS were not common after ankle sprain. However, they still merit consideration as postinjury sequelae, especially in patients with persistent symptoms. Increasing age, type of sprain, female sex, metabolic syndrome, and active-duty status were all significantly associated with the development of one or both subsequent injuries. This work provides normative data for incidence rates of these subsequent injuries and can help increase awareness of these conditions, leading to improved management of refractory ankle sprain injuries.
Keywords: ankle; sprain; posterior tibial tendon; tarsal tunnel syndrome; odds ratio